Comportamento sedentário e fatores associados em adolescentes do Nordeste do Brasil - Silva, Fabiana Medeiros de Almeida (2016)
Introduction: Sedentary behavior is the term used to describe activities energy expenditure close to resting values and normally performed in sitting position. Aims: To analyze the factors associated with exposure to sedentary behavior in adolescents. Methods: This study is a secondary analysis of data of an epidemiological cross-sectional survey with a representative sample of high school students enrolled in Public State Schools of Sergipe/Brazil, with sample composed of 3,992 adolescents aged 14-19 years. Data were collected through self-administered questionnaire. The time spent in activities such as watching television, playing computer games, chatting with friends, playing cards or dominoes was used as a measure of sedentary behavior (> 2 hours/day = exposed). Variables such as level of physical activity, smoking, drug use, consumption (fruits and vegetables, soft drinks, alcohol), psychosocial stress indicators (stress perception, feelings of loneliness, trouble sleeping), demographic factors (gender, age, skin color) socioeconomic factors (school grade, school shift, failure, place of residence, maternal schooling, occupational status and family) income were analyzed. Binary logistic regression was used to analyze association among variables. Results: The prevalence of exposure to sedentary behavior was 46.7% and was associated with low levels of physical activity (OR=1.18; IC95% 1.01-1.38), consumption of soft drinks (OR=1.26; IC95% 1.10-1.43), negative stress perception (OR=1.31; IC95% 1.12-1.53), feelings of loneliness (OR=1.19; IC 95% 1.05-1.36), trouble sleeping (OR=1.20; IC 95% 1.05-1.37), female gender (OR=1,33; IC95% 1,14-1,55), younger age group (OR=1,51; IC95% 1,18-1,94), first grades of high school (OR=1,29; IC95% 1,05-1,59), day school shift (OR=1,25; IC95% 1,08-1,46), place of residence in urban areas (OR=1,25; IC95% 1,08-1,46), higher maternal schooling, not working (OR=1,58; IC95% 1,21-2,06) and higher economic class (OR=2,22; IC95% 1,82-2,72). Conclusions: This study showed high proportion of adolescents exposed to sedentary behavior and association with demographic, socioeconomic and behavioral characteristics of adolescents. Interventions should be implemented to reduce exposed to sedentary behavior among young people, especially in subgroups of greater exposure.